Participation in the Post-Lomé process : an analysis of the issues and negotiating option - Huggins, George (ECDPM MaastrichtNL, 1997)
Examines some of the major issues of interest to the ACP and the EU countries regarding participation and development. Analyzes their relevance in the context of the debate on cooperation and assesses and explores some negotiation options and strategies for consideration by the ACP group during the forthcoming negotiations.